Biochemical passivation of metal surfaces for sensor application: reactive annealing of polycrystalline gold films in hydrogen sulfide atmosphere - Snopok, B. A.; Kostyukevych, K.V.; Beketov, G.V.; Zinio, S.A.; Shirshov, Yu.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The formation of AuxSy interfacial layer by reactive annealing of gold films in H₂S atmosphere is investigated. This seems to be a technologically favorable technique for the large-scale and low-cost fabrication of nondestructive immobilization support for biological molecules. Formation of phases with different chemical functionality and surface topography as a function of reaction time was studied using Atomic Force Microscopy (AFM), Surface Plasmon Resonance (SPR) measurements and biomolecular interaction analysis (trypsin - Soybean Trypsin Inhibitor (STI) reaction). The results obtained confirm the classical two-step model for the sulfide phase formation during reactive annealing. This includes an intermediate formation of a dispersed phase of sulfur followed by its reconstruction to a close-packed sulfide layer. Adsorption of proteins onto a certain sulfide layer passes with retention of a native state of adsorbed molecules. The proposed strategy for formation of biochemical structures (gold/sulfide/proteins) on the surface of physical transducers opens a new way for design and development of novel artificial smart sensing systems. They not only maintain optimal functioning of bioreceptors but also are responsive to their environment.